Modified Mindfulness-Based Stress Reduction (MBSR) Therapy to Reduce Psychological Distress in Chronic Kidney Disease (CKD) Patients on Haemodialysis (HD) - Arsyi, Dila Nurul; Natashia, Dhea; Gayatri, Dewi; Irawati, Diana; Jumaiyah, Wati; Nuraini, Tuti (GLOBAL HEALTH SCIENCE GROUP, 2024)
Chronic Kidney Disease (CKD), is a disease with high mortality and mortality, so it requires lifelong hemodialysis (HD) management, this will trigger psychological distress which increases the risk of worsening in CKD. So, it is necessary to give non-pharmacological therapies, one of which is a modification of Mindfulness-Based Stress Reduction (MBSR) Therapy. Objective: The purpose of this study was to determine the effect of MBSR therapy modification on psychological distress in CKD patients. Method: Quasi-experiment with pretest-posttest control group approach. A population of 44 respondents with a sample of 29 respondents using a simple random sampling technique. Measurement of psychological distress variables using the Kessler Pshycological Distress Scale-10 (K-10). MBSR modification therapy intervention has 4 sessions in one treatment, applied 7 days with a total duration of 30 minutes. Data analysis using paired t-test and independent t-test. Results: The results showed that the mean scores of Psychological Distress intervention group (21.7 (pre-test); 17.1 (post-test)), control group (18.8 (pre-test); 18.5 (post-test)). There were differences in mean psychological distress scores between the intervention and control groups (MD=4.38, t=5.92 (95%CI, 2.81; 5.95), p < 0.001, d=2.22). Conclusions: MBSR modification therapy can be used to reduce psychological distress in patients.